Scratch-resistant UV curing wood board and processing technology thereof
By combining modified inorganic nanoparticles with specific acrylate monomers and photoinitiators, high-performance UV cured paint is formed, which solves the problems of low surface hardness and poor flame retardancy of existing UV cured wood panels, and achieves higher surface hardness and flame retardant performance.
Patent Information
- Application Number
- CN202311353868.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
The existing UV cured wood panels have problems such as low surface hardness, reduced mechanical properties due to internal stress defects, and poor dispersion and compatibility of flame retardant UV cured paint.
The inorganic nanoparticles were modified with silane coupling agent and mixed with epoxy acrylate, piperazinyl acrylate, piperidinyl acrylate, pentaerythritol triacrylate and photoinitiator to form a UV cured paint, and the surface hardness and flame retardant properties of the wooden board are improved through vacuum impregnation and double-lantern curing processes.
It significantly improves the surface hardness and flame retardant properties of UV cured wood boards, enhances its scratch and wear resistance, while reducing internal stress and improving the overall mechanical properties.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scratch-resistant wood boards, in particular to a scratch-resistant UV-cured wood board and a processing technology thereof. Background Art
[0002] UV-cured wood board is a decorative board whose surface is treated and protected by ultraviolet light-curing paint, thereby enhancing its chemical resistance, moisture resistance, and deformation resistance.
[0003] In the existing process, UV-cured wood boards have the following defects: (1) Low surface hardness; surface hardness is an important indicator for evaluating its physical damage resistance. Generally, the hardness needs to be above 2H to effectively resist physical defects such as scratches. However, the current UV-cured wood boards are generally 3H; therefore, the surface hardness of UV-cured wood boards still needs to be further improved. (2) The UV-curing paint used for UV-cured wood boards has a fast light curing rate, which leads to internal stress defects and thus a decrease in mechanical properties; secondly, the presence of trace oxygen slows down the curing rate, resulting in partial curing and local deformation, leading to a decrease in physical properties; (3) The existing flame-retardant UV-curing paint has different properties between the flame retardant and the resin, resulting in poor dispersibility and compatibility, resulting in poor mechanical properties.
[0004] In summary, solving the above problems and preparing a UV-cured wood board with good flame retardancy and scratch resistance is of great value. Summary of the invention
[0005] The object of the present invention is to provide a scratch-resistant UV-cured wood board and a processing technology thereof to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A processing technology for scratch-resistant UV-cured wood board, including the following process:
[0008] S1: polishing the surface of the wood substrate to be smooth, vacuum impregnating the surface of the wood substrate in an acrylic ester monomer solution, and drying the surface to obtain a pretreated wood substrate;
[0009] S2: using a silane coupling agent to modify inorganic nanoparticles to obtain modified inorganic nanoparticles; mixing the modified inorganic nanoparticles with epoxy acrylate, piperazine acrylate, piperidinyl acrylate, pentaerythritol triacrylate, and a photoinitiator to obtain a UV curing paint;
[0010] S3: coating the surface of the pretreated substrate with UV curing paint and curing it under an inert atmosphere to obtain a scratch-resistant UV-cured wood board.
[0011] More optimally, the acrylic ester monomer solution comprises the following components: by weight, 100 parts of ethanol, 0.5-1 parts of glycidyl acrylate, 1-1.5 parts of hydroxyethyl acrylate, 1-1.5 parts of dihydroeugenol acrylate, and 0.1-0.5 parts of thermal initiator.
[0012] More optimally, during the vacuum impregnation process: the pressure is -0.08 to -0.09 MPa, and the impregnation time is 2 to 4 hours; during the drying process: drying at 50 to 60°C for 2 to 3 hours, and drying at 60 to 80°C for 24 hours.
[0013] More optimally, the UV curing paint comprises the following components: by weight, 50 to 60 parts of epoxy acrylate, 17 to 20 parts of piperazine acrylate, 8 to 10 parts of piperidinyl acrylate, 10 to 12 parts of pentaerythritol triacrylate, 3 to 5 parts of inorganic nanoparticles, and 2 to 3 parts of photoinitiator; the silane coupling agent in the modified inorganic nanoparticles accounts for 4 to 5wt% of the nanoparticles.
[0014] More optimally, the preparation method of the piperazinyl acrylate is as follows: anhydrous piperazine, glycidyl acrylate, and p-aminobenzenesulfonic acid are uniformly mixed, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperazine monomer; piperazine monomer and triethylamine are uniformly mixed, and diphenyl chlorophosphate is added dropwise under a nitrogen atmosphere, and reacted at room temperature for 4 to 5 hours, filtered to remove impurities, and the solution is evaporated to remove the solvent to obtain piperazinyl acrylate;
[0015] The preparation method of the piperidinyl acrylate comprises the following steps: piperidine, glycidyl acrylate and p-aminobenzenesulfonic acid are uniformly mixed, reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperidine monomer; cystamine diisocyanate is added to anhydrous toluene and mixed uniformly, heated to 70-80° C. under a nitrogen atmosphere, an organic tin-toluene solution is added, a piperidine monomer-toluene solution is added dropwise, reacted for 2-3 hours, and post-treated to obtain the piperidinyl acrylate.
[0016] Preferably, the wood board substrate is Australian pine board; the inorganic nanoparticles include but are not limited to one or more of nano zinc dioxide, nano silicon dioxide, and nano titanium dioxide; the silane coupling agent is a silane coupling agent containing unsaturated functions, including but not limited to one or more of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, and allyltriethoxysilane; and the photoinitiator is a TPO-type photoinitiator.
[0017] More optimally, the raw materials of the piperazine acrylate include the following components: by weight, 15 parts of piperazine monomer, 3 to 3.5 parts of triethylamine, and 24 to 28 parts of diphenyl chlorophosphate; the piperazine monomer includes the following raw materials: by weight, 4.8 to 5.3 parts of anhydrous piperazine, 14 to 16 parts of glycidyl acrylate, and 0.5 to 0.8 parts of p-aminobenzenesulfonic acid.
[0018] More optimally, the raw materials of the piperidinyl acrylate include the following components: by weight: 5 parts of cystamine diisocyanate, 0.05-0.08 parts of organotin, and 5.5-5.8 parts of piperidine monomer; the piperidine monomer includes the following raw materials: by weight: 4.8-5.3 parts of piperidine, 7-8 parts of glycidyl acrylate, and 0.5-0.8 parts of p-aminobenzenesulfonic acid.
[0019] Preferably, the coating thickness of the UV curing paint is 0.3-0.4 mm; during the curing process of the UV curing paint: dual lamp curing is used, and the xenon lamp curing light intensity is 100-150 mW / cm 2 , the light intensity of high pressure mercury lamp is 90~100mW / cm 2 ; The curing time is 1 to 2 minutes.
[0020] More optimally, a scratch-resistant UV-cured wood board processing process is used to obtain a scratch-resistant UV-cured wood board.
[0021] Compared with the prior art, the beneficial effects are as follows:
[0022] (1) The scheme uses an acrylate monomer solution for vacuum impregnation. The acrylate monomers in the solution include glycidyl acrylate and hydroxyethyl acrylate, which have smaller molecular structures and are more soluble in the cell wall structure of the wood board than UV curing paint, and can produce an interfacial effect with the cell wall structure of the wood board, thereby improving the strength of the wood board. At the same time, it contains dihydroeugenol acrylate, which has a structure similar to the lignin structure in the wood board, thereby promoting the impregnation. In addition, the acrylate monomer solution contains a thermal initiator, which can be cross-linked in the wood board during the drying process, and the unreacted groups can be photo-cross-linked with the UV curing paint on the surface, thereby improving the interfacial effect.
[0023] In the (2) scheme, two acrylate monomers (piperazine acrylate and piperidinyl acrylate) were prepared based on piperazine and piperidine, and the two were mixed with pentaerythritol triacrylate to form a diluent, and then mixed with epoxy acrylate to form the main body of the UV curing paint; and the modified inorganic nanoparticles and photoinitiator were introduced to form the UV curing paint. The flame retardant properties were effectively enhanced on the basis of improving the surface properties.
[0024] Piperazine acrylate is firstly grafted with glycidyl acrylate by reacting amino groups with epoxy groups, and then grafted with diphenyl chlorophosphate by reacting hydroxyl groups formed by the grafting reaction with chlorine, thereby forming piperazine acrylate with flame retardancy; wherein the grafting of diphenyl chlorophosphate not only increases the flame retardancy, but also increases the affinity with epoxy acrylate due to the phenyl group contained; and enhances the rigidity and improves the wear resistance;
[0025] Among them, piperidinyl acrylate is firstly prepared by reacting amino groups with epoxy groups to graft glycidyl acrylate, and then the hydroxyl groups formed by the grafting reaction are reacted with isocyanate to graft the piperidinyl monomer onto the two ends of cystamine diisocyanate, thereby forming piperidinyl acrylate with a disulfide bond; wherein, piperidinyl acrylate is also flame retardant and can assist and synergize piperazinyl acrylate in enhancing flame retardancy; and the disulfide bond contained is a reversible bond, which can help enhance chain breaking movement and cause cross-linking reformation, thereby reducing the internal stress of UV curing and improving the surface mechanical properties.
[0026] (3) In the scheme, the type and content of the photoinitiator are limited. The reason is that the type and content of photocuring have a certain influence on the surface hardness. Compared with photoinitiators such as Irgacure500, TPO initiator has better introduction and photocuring performance. Regarding the content, in general, in order to enhance the efficiency of photocuring, a larger amount of photoinitiator will be introduced. However, introducing more will result in a shorter polymer matrix chain length, resulting in lower hardness. In addition, the residual photoinitiator will produce side effects such as yellowing and degradation.
[0027] Of course, when the photoinitiator content is low, it may affect the photocuring rate, resulting in poor curing performance. Therefore, in this scheme, tertiary amines of piperazine acrylate and piperidinyl acrylate are used to effectively enhance the efficiency of photoinitiated polymerization and make up for the disadvantage of low photoinitiator content. At the same time, dual-lamp curing and inert gas curing atmosphere are used to effectively inhibit the effect of trace oxygen, thereby improving photocuring performance, inhibiting defects, and improving surface performance. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and exemplarily include: the following parts are by mass; anhydrous piperazine (CAS: 110-85-0), piperidine (CAS: 110-89-4), diphenyl chlorophosphate (CAS: 2524-64-3), glycidyl acrylate (CAS: 106-90-1), p-aminobenzenesulfonic acid (CAS: 121-57-3), hydroxyethyl acrylate (CAS: 818-61-1), epoxy acrylate (brand is Jusheng, item number is JS7516), pentaerythritol triacrylate (CAS: 3524-68-3), TPO photoinitiator (Chivacure TPO photoinitiator, provided by Shanghai Puzhan Industrial Co., Ltd.); Preparation of dihydroeugenol acrylate: 5 parts of dihydroeugenol, 0.8 parts of triethylamine, and 0.003 parts of p-hydroxyanisole are added to 10 parts of THF in sequence and mixed evenly, 2.7 parts of acryloyl chloride are added dropwise under an ice bath, and the mixture is reacted at 40°C for 5 hours, and post-treated to obtain dihydroeugenol acrylate; Preparation of cystamine diisocyanate: 9 parts of triphosgene are introduced into 50 parts of anhydrous dichloromethane to obtain reaction solution A; 11 parts of cystamine dihydrochloride and 23 parts of pyridine are added to 150 parts of anhydrous dichloromethane, and reaction solution A is added dropwise under an ice bath; after the addition is completed, the mixture is reacted at -10°C for 6 hours, extracted, and dried to obtain cystamine diisocyanate.
[0030] Embodiment 1: A processing technology for a scratch-resistant UV-cured wood board, comprising the following process:
[0031] S1: (1) Add 0.6 parts of glycidyl acrylate, 1.4 parts of hydroxyethyl acrylate, 1.5 parts of dihydroeugenol acrylate and 0.3 parts of azobisisobutyronitrile to 100 parts of ethanol in sequence and mix well to obtain an acrylate monomer solution; (2) Polish the surface of the Australian pine board to make it smooth, and vacuum immerse it in the acrylate monomer solution: pressure -0.0859MPa, immersion time is 3 hours; Dry: dry at 60°C for 2 hours and at 80°C for 24 hours to obtain a pretreated wood board;
[0032] S2: (1) The preparation method of the piperazine acrylate is as follows: 5 parts of anhydrous piperazine, 15 parts of glycidyl acrylate and 0.6 parts of p-aminobenzenesulfonic acid are mixed evenly, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperazine monomer; 15 parts of a piperazine monomer and 3.2 parts of triethylamine are mixed evenly, and 26 parts of diphenyl chlorophosphate are added dropwise under a nitrogen atmosphere, and reacted at room temperature for 4 to 5 hours, filtered to remove impurities, and the solution is evaporated to remove the solvent to obtain piperazine acrylate;
[0033] (2) The preparation method of the piperidinyl acrylate is as follows: 5 parts of piperidine, 7.5 parts of glycidyl acrylate, and 0.6 parts of p-aminobenzenesulfonic acid are mixed evenly, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperidine monomer; 5 parts of cystamine diisocyanate are added to 50 parts of anhydrous toluene and mixed evenly, and the mixture is heated to 80° C. under a nitrogen atmosphere, and an organic tin-toluene solution (0.08 parts of dibutyltin dilaurate and 10 parts of toluene) is added, and a piperidine monomer-toluene solution (5.6 parts and 20 parts of toluene) is added dropwise, and the mixture is reacted for 3 hours, and post-treated to obtain piperidinyl acrylate;
[0034] (3) Dispersing 5 parts of nano zinc oxide and methacryloxypropyltrimethoxysilane (accounting for 5 wt% of the nanoparticles) in 150 parts of anhydrous toluene, uniformly dispersing by ultrasonication, adding to reflux for 2 hours, cooling and centrifuging for washing, and obtaining modified nanoparticles;
[0035] (4) the modified nanoparticles were mixed with 54.5 parts of epoxy acrylate, 18 parts of piperazine acrylate, 10 parts of piperidinyl acrylate, 10 parts of pentaerythritol triacrylate, and 2.5 parts of TPO photoinitiator to obtain a UV curing paint;
[0036] S3: UV curing paint is applied to the surface of the pre-treated substrate with a coating thickness of 0.35 mm. Double lamps are used for curing in a nitrogen atmosphere with a xenon lamp curing light intensity of 120 mW / cm 2 , the light intensity of the high pressure mercury lamp is 100mW / cm 2 ; The curing time is 80 seconds; a scratch-resistant UV-cured wood board is obtained.
[0037] Embodiment 2:
[0038] S1: (1) Add 0.5 parts of glycidyl acrylate, 1.5 parts of hydroxyethyl acrylate, 1 part of dihydroeugenol acrylate, and 0.3 parts of azobisisobutyronitrile to 100 parts of ethanol in sequence, mix well, and obtain an acrylate monomer solution; (2) Polish the surface of the Australian pine board to make it smooth, and vacuum immerse it in the acrylate monomer solution: pressure -0.0859MPa, immersion time is 3 hours; Dry: dry at 60°C for 2 hours, and dry at 80°C for 24 hours to obtain a pretreated wood board;
[0039] S2: (1) The preparation method of the piperazine acrylate is as follows: 5 parts of anhydrous piperazine, 15 parts of glycidyl acrylate and 0.6 parts of p-aminobenzenesulfonic acid are mixed evenly, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperazine monomer; 15 parts of a piperazine monomer and 3.2 parts of triethylamine are mixed evenly, and 26 parts of diphenyl chlorophosphate are added dropwise under a nitrogen atmosphere, and reacted at room temperature for 4 to 5 hours, filtered to remove impurities, and the solution is evaporated to remove the solvent to obtain piperazine acrylate;
[0040] (2) The preparation method of the piperidinyl acrylate is as follows: 5 parts of piperidine, 7.5 parts of glycidyl acrylate, and 0.6 parts of p-aminobenzenesulfonic acid are mixed evenly, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperidine monomer; 5 parts of cystamine diisocyanate are added to 50 parts of anhydrous toluene and mixed evenly, and the mixture is heated to 80° C. under a nitrogen atmosphere, and an organic tin-toluene solution (0.08 parts of dibutyltin dilaurate and 10 parts of toluene) is added, and a piperidine monomer-toluene solution (5.6 parts and 20 parts of toluene) is added dropwise, and the mixture is reacted for 3 hours, and post-treated to obtain piperidinyl acrylate;
[0041] (3) dispersing 4 parts of nano zinc oxide and methacryloxypropyltrimethoxysilane (accounting for 5 wt% of the nanoparticles) in 150 parts of anhydrous toluene, uniformly dispersing by ultrasonication, adding to reflux for 2 hours, cooling and centrifuging for washing, and obtaining modified nanoparticles;
[0042] (4) the modified nanoparticles were mixed with 52 parts of epoxy acrylate, 20 parts of piperazine acrylate, 10 parts of piperidinyl acrylate, 12 parts of pentaerythritol triacrylate, and 2 parts of TPO photoinitiator to obtain a UV curing paint;
[0043] S3: UV curing paint is applied to the surface of the pre-treated substrate with a coating thickness of 0.35 mm. Double lamps are used for curing in a nitrogen atmosphere with a xenon lamp curing light intensity of 120 mW / cm 2 , the light intensity of the high pressure mercury lamp is 100mW / cm 2 ; The curing time is 80 seconds; a scratch-resistant UV-cured wood board is obtained.
[0044] Embodiment 3:
[0045] S1: (1) Add 1 part of glycidyl acrylate, 1 part of hydroxyethyl acrylate, 1 part of dihydroeugenol acrylate, and 0.3 part of azobisisobutyronitrile to 100 parts of ethanol in sequence, mix well, and obtain an acrylate monomer solution; (2) Polish the surface of the Australian pine board to make it smooth, and vacuum immerse it in the acrylate monomer solution: pressure -0.0859MPa, immersion time is 3 hours; Dry: dry at 60°C for 2 hours, and dry at 80°C for 24 hours to obtain a pretreated wood board;
[0046] S2: (1) The preparation method of the piperazine acrylate is as follows: 5 parts of anhydrous piperazine, 15 parts of glycidyl acrylate and 0.6 parts of p-aminobenzenesulfonic acid are mixed evenly, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperazine monomer; 15 parts of a piperazine monomer and 3.2 parts of triethylamine are mixed evenly, and 26 parts of diphenyl chlorophosphate are added dropwise under a nitrogen atmosphere, and reacted at room temperature for 4 to 5 hours, filtered to remove impurities, and the solution is evaporated to remove the solvent to obtain piperazine acrylate;
[0047] (2) The preparation method of the piperidinyl acrylate is as follows: 5 parts of piperidine, 7.5 parts of glycidyl acrylate, and 0.6 parts of p-aminobenzenesulfonic acid are mixed evenly, and reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperidine monomer; 5 parts of cystamine diisocyanate are added to 50 parts of anhydrous toluene and mixed evenly, and the mixture is heated to 80° C. under a nitrogen atmosphere, and an organic tin-toluene solution (0.08 parts of dibutyltin dilaurate and 10 parts of toluene) is added, and a piperidine monomer-toluene solution (5.6 parts and 20 parts of toluene) is added dropwise, and the mixture is reacted for 3 hours, and post-treated to obtain piperidinyl acrylate;
[0048] (3) dispersing 3 parts of nano zinc oxide and methacryloxypropyltrimethoxysilane (accounting for 5 wt% of the nanoparticles) in 150 parts of anhydrous toluene, uniformly dispersing by ultrasonication, adding to reflux for 2 hours, cooling and centrifuging for washing, and obtaining modified nanoparticles;
[0049] (4) the modified nanoparticles were mixed with 59 parts of epoxy acrylate, 17 parts of piperazine acrylate, 8 parts of piperidinyl acrylate, 10 parts of pentaerythritol triacrylate, and 3 parts of TPO photoinitiator to obtain a UV curing paint;
[0050] S3: UV curing paint is applied to the surface of the pre-treated substrate with a coating thickness of 0.35 mm. Double lamps are used for curing in a nitrogen atmosphere with a xenon lamp curing light intensity of 120 mW / cm 2 , the light intensity of the high pressure mercury lamp is 100mW / cm 2 ; The curing time is 80 seconds; a scratch-resistant UV-cured wood board is obtained.
[0051] Comparative Example 1: Cystamine diisocyanate was replaced with 1,6-hexamethylene diisocyanate, and the remaining steps were the same as those in Example 1.
[0052] Comparative Example 2: piperazine acrylate was replaced by 1,6-hexanediol diacrylate; piperidinyl acrylate was replaced by triethylene glycol diacrylate; the remaining steps were the same as in Example 1.
[0053] Comparative Example 3: The mass parts of piperazine acrylate and piperidinyl acrylate were exchanged, and the remaining steps were the same as those in Example 1.
[0054] Comparative Example 4: The photoinitiator was replaced with Irgacure 500, and the remaining steps were the same as those in Example 1.
[0055] Performance test 1: The scratch-resistant UV wood board prepared in the embodiment and comparative example was scratched on the surface with a length of 3 cm at a 40° angle with a vertical pressure of 1 kg, and repeated 5 times according to the method of GB / T15036.2. If there is no scratch on the surface, the surface hardness can be determined. The UV curing paint obtained in the embodiment and comparative example was cured to form a film layer, and its limiting oxygen index was tested according to ASTMD2863 to judge the flame retardancy. The obtained data are shown in the following table:
[0056] Surface hardness LOI(%) Example 1 5H 33.2 Example 2 5H 32.4 Example 3 4H 31.3 Comparative Example 1 4H 30.8 Comparative Example 2 3H 23.5 Comparative Example 3 4H 28.9 Comparative Example 4 4H 33.1
[0057] Performance test 2: The scratch-resistant UV wood board prepared in Example 1 was subjected to a 100-minute wear at a force of 5 N using a paint film wear instrument according to the method of GB / T15036.2. The wear value was 34 mg, and the surface had excellent wear resistance.
[0058] Conclusion: From the data of Example 1, it can be seen that in this application, Australian pine board is used as the substrate, and UV curing paint is coated on the surface. After double-lamp curing, a scratch-resistant UV-cured wood board with a smooth and bright surface is obtained, the color is long-lasting and the paint does not fall off, and the surface hardness is high, wear-resistant and scratch-resistant, and durable. At the same time, the surface paint film has good flame retardancy, which can increase the safety of application. Comparing the data of Example 1 with the data of Comparative Examples 1 to 4, it can be seen that in Comparative Example 1, since cystamine diisocyanate is replaced with 1,6-hexamethylene diisocyanate, stress defects are increased, thereby reducing the surface performance; in Comparative Example 2, since piperazine acrylate and piperazine acrylate are not introduced, all performances are greatly reduced; in Comparative Example 3, due to the interchange of the mass parts of piperazine acrylate and piperidine acrylate, the surface hardness and flame retardancy are reduced; in Comparative Example 4, due to the change of the photoinitiator Irgacure500, the surface performance is significantly reduced.
[0059] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for a scratch-resistant UV-cured wood board, characterized in that: Including the following process: S1: The surface of the wood substrate is polished smooth and vacuum impregnated in an acrylate monomer solution; drying to obtain a pretreated wood board; S2: using a silane coupling agent to modify inorganic nanoparticles to obtain modified inorganic nanoparticles; mixing the modified inorganic nanoparticles with epoxy acrylate, piperazine acrylate, piperidinyl acrylate, pentaerythritol triacrylate, and a photoinitiator to obtain a UV curing paint; S3: coating the surface of the pretreated substrate with UV curing paint and curing it under an inert atmosphere to obtain a scratch-resistant UV-cured wood board.
2. The processing technology of a scratch-resistant UV-cured wood board according to claim 1, characterized in that: The acrylic acid ester monomer solution comprises the following components: by weight, 100 parts of ethanol, 0.5-1 parts of glycidyl acrylate, 1-1.5 parts of hydroxyethyl acrylate, 1-1.5 parts of dihydroeugenol acrylate, and 0.1-0.5 parts of thermal initiator.
3. The processing technology of a scratch-resistant UV-cured wood board according to claim 1, characterized in that: During the vacuum impregnation process: the pressure is -0.08 to -0.09 MPa, and the impregnation time is 2 to 4 hours; during the drying process: drying at 50 to 60°C for 2 to 3 hours, and drying at 60 to 80°C for 24 hours.
4. The processing technology of a scratch-resistant UV-cured wood board according to claim 1, characterized in that: The UV curing paint comprises the following components: by weight, 50-60 parts of epoxy acrylate, 17-20 parts of piperazine acrylate, 8-10 parts of piperidinyl acrylate, 10-12 parts of pentaerythritol triacrylate, 3-5 parts of inorganic nanoparticles, and 2-3 parts of photoinitiator; the silane coupling agent in the modified inorganic nanoparticles accounts for 4-5wt% of the nanoparticles.
5. The processing technology of the scratch-resistant UV-cured wood board according to claim 4, characterized in that: The preparation method of the piperazine acrylate is as follows: anhydrous piperazine, glycidyl acrylate and p-aminobenzenesulfonic acid are uniformly mixed, and the mixture is reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperazine monomer; the piperazine monomer and triethylamine are uniformly mixed, and diphenyl chlorophosphate is added dropwise under a nitrogen atmosphere to react at room temperature for 4 to 5 hours, and the mixture is filtered to remove impurities, and the solvent is removed by rotary evaporation to obtain the piperazine acrylate; The preparation method of the piperidinyl acrylate comprises the following steps: piperidine, glycidyl acrylate and p-aminobenzenesulfonic acid are uniformly mixed, reacted at room temperature for 24 hours under a nitrogen atmosphere to obtain a piperidine monomer; cystamine diisocyanate is added to anhydrous toluene and mixed uniformly, heated to 70-80° C. under a nitrogen atmosphere, an organic tin-toluene solution is added, a piperidine monomer-toluene solution is added dropwise, reacted for 2-3 hours, and post-treated to obtain the piperidinyl acrylate.
6. The processing technology of the scratch-resistant UV-cured wood board according to claim 1, characterized in that: The wood board substrate is Australian pine board; the inorganic nanoparticles include one or more of nano zinc dioxide, nano silicon dioxide, and nano titanium dioxide; the silane coupling agent is a silane coupling agent containing unsaturated functions, including one or more of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, and allyltriethoxysilane; the photoinitiator is a TPO-type photoinitiator.
7. The processing technology of the scratch-resistant UV-cured wood board according to claim 5, characterized in that: The raw materials of the piperazine acrylate include the following components: by weight, 15 parts of piperazine monomer, 3 to 3.5 parts of triethylamine, and 24 to 28 parts of diphenyl chlorophosphate; the piperazine monomer includes the following raw materials: by weight, 4.8 to 5.3 parts of anhydrous piperazine, 14 to 16 parts of glycidyl acrylate, and 0.5 to 0.8 parts of p-aminobenzenesulfonic acid.
8. The processing technology of the scratch-resistant UV-cured wood board according to claim 5, characterized in that: The raw materials of the piperidinyl acrylate include the following components: by weight; 5 parts of cystamine diisocyanate, 0.05-0.08 parts of organotin, 5.5-5.8 parts of piperidine monomer; the piperidine monomer includes the following raw materials: calculated by weight; 4.8-5.3 parts of piperidine, 7-8 parts of glycidyl acrylate, and 0.5-0.8 parts of p-aminobenzenesulfonic acid.
9. The processing technology of the scratch-resistant UV-cured wood board according to claim 5, characterized in that: The coating thickness of the UV curing paint is 0.3-0.4 mm; during the curing process of the UV curing paint: dual lamp curing is used, and the xenon lamp curing light intensity is 100-150 mW / cm 2 , the light intensity of high pressure mercury lamp is 90~100mW / cm 2 ; The curing time is 1 to 2 minutes.
10. A scratch-resistant UV-cured wood board obtained by processing the scratch-resistant UV-cured wood board according to any one of claims 1 to 9.
Citation Information
Patent Citations
Solid wood composite floor based on inorganic nanoparticle modified SMF resin coating
CN111975887A
Silica sol-hydroxy acrylic resin composite-dispersion and preparation method thereof
CN115584175A
Surface treatment process of flame-retardant wood board
CN115972329A
Laminate support
CN210539980U
Surface coating method
KR100798414B1